Development of information competence of students in conditions of digitalisation and mathematisation - Shybut, Iryna P. (Journal of the Belarusian State University. Journalism, 2023)
The author’s experience of developing computer disciplines for training students of the faculty of journalism of the Belarusian State University is considered. It is emphasised that the importance of forming a transprofessional model for the development of information competence of university students in the context of digitalisation and mathematisation, a variant of the methodology for updating the development of educational and methodological materials, primarily digital ones, is determined. The article substantiates the position that when training a modern specialist, it is necessary to pay attention on the process of developing information competence and the transition to transprofessionalism through a combination of related professions, transdisciplinary synthesis of knowledge. Examples of the active use of project-type heuristic tasks and distance learning technologies during the educational process at the faculty of journalism of the Belarusian State University, which is based on the principles of Internet education of a creative type, are given.
Keywords: digitalisation; transprofessionalism; mathematisation; information and communication technologies; educational process; information competence; digital educational environment